Aquatic Fungi from Nasik District-I - D, C.S. Jadhav, Patil, S. Y. and Borse, B. (Recent Research in Science and Technology, 2011)
The paper deals with five species of aquatic fungi belonging to five genera of freshwater hyphomycetes found in foam samples collected from Trambkeshwar stream of Nasik District. The foam spora of this region represents mixture of both tropical and temperate species. Brief notes and illustration are given for each taxon. Geographical distribution of each species in India is also provided.